Use of modern metegenomics approaches in evaluation of soil microbiota of West Kazakhstan area (Experimental biology, 2015)
This article describes a method to assess the soil microbiome with application of modern metagenomics. The method to clean soil DNA using adsorption on purified silicon. Identified data for optimization of PCR primer design. To assess the soil metagenome library composed of amplicons and held its initial analysis. Revealed the most prevalent phyla inthese soil samples.
Keywords: microbiome; soil microorganisms; PCR; sequencing; taxonomy; soil type; DNA; agroecology; monitoring; molecular biology